(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
The aim of this study is know the five leadership practices according to the theory of network of leadership by Black and Mouton for the presidents of the Taxation General Board from their prospective, that is through answering the questionnaire questions. To achieving the objectives of this study, the researcher organized a questionnaire form as a main instrument for data collection. It includes (30) items distributed into five leadership practices according to the theory of network of leadership. Each one is subdivided into (6) questions. The questionnaire was distributed to the presidents of the Taxation General Board of (14). The researcher used the SPSS program to analyses the answers. Through the answers, he came to the results that: • (team leadership practice) achieved the highest rate of agreement (% 87) of the study community. • (Mid-way or the mercury leadership practice) achieved the highest rate of agreement (% 80). • (Task manager or diligent leadership practice) achieved the highest rate of agreement (% 77). • (social club leadership practice) achieved the rate of agreement (% 75). • (tolerate of bureaucratic leadership practice) achieved the lowest rate of agreement (% 30). In the light of the results, the researcher came up to the recommendations, like: • Support the efforts of head of Department in the field of holding training courses for inspectors and assessors, and give the incentives. • Increase the capacities granted to contribute effectively to solve disputes and make settlements. • Work on putting a list to determine the standards of performance for each section to encourage the presidents of departments and the employees to attain on knowing the negative performance for each employee. Put certain restricts to commission negotiation by the heads of the president of department so that the effective commission could be achieved and in the time.